2011
DOI: 10.1094/mpmi-08-10-0194
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Signaling and Transport Promote Susceptibility to the Root-Infecting Fungal Pathogen Fusarium oxysporum in Arabidopsis

Abstract: Fusarium oxysporum is a root-infecting fungal pathogen that causes wilt disease on a broad range of plant species, including the model plant Arabidopsis thaliana. Currently, very little is known about the molecular or physiological processes that are activated in the host during infection and the roles these processes play in resistance and susceptibility to F. oxysporum. In this study, we analyzed global gene expression profiles of F. oxysporum-infected Arabidopsis plants. Genes involved in jasmonate biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
150
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 105 publications
7
150
0
1
Order By: Relevance
“…brassicicola (Qi et al 2012). Many soil-borne pathogens infect the roots through auxin-rich regions (Kazan and Manners 2009), such as the root-infection fungus Fusarium oxysporum , which infection leads to alteration in auxin homeostasis (Kidd et al 2011). Arabidopsis mutants defective in auxin signalling show increased resistance to F. oxysporum (Kidd et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…brassicicola (Qi et al 2012). Many soil-borne pathogens infect the roots through auxin-rich regions (Kazan and Manners 2009), such as the root-infection fungus Fusarium oxysporum , which infection leads to alteration in auxin homeostasis (Kidd et al 2011). Arabidopsis mutants defective in auxin signalling show increased resistance to F. oxysporum (Kidd et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici was studied at different stages of signaling using mutants defective in the eT (ein2-5), JA (co1-1 and jar1-1) and SA (NahG, (Berrocal-Lobo and Molina 2004) pathways, revealing the influence of these pathways against Fox. Thatcher et al (2009), have demonstrated JA perception mutant coronatine insensitive 1 (coi1), but not JA biosynthesis mutants, which exhibited a high level of resistance to wilt disease caused by F. oxysporum in Arabidopsis Kidd et al (2011) thaliana. Recently a novel transcription factor, LBD20 (Lateral Organ Boundaries Domain) gene which on its disruption led to increased resistance in Arabidopsis to Fox was found and this suggests that LBD20 is a Fusarium susceptibility gene that appears to regulate components of JA-signaling downstream of COI1 and MYC2 transcription factors (Thatcher et al 2012a).…”
Section: Salicylic Acid (Sa) Jasmonic Acid (Ja) and Ethylene (Et)mentioning
confidence: 99%
“…Recently it has been reported that Arabidopsis mutants with altered auxin and tryptophan-derived metabolites such as indole-glucosinolates and camalexin did not show an altered resistance to F. oxysporum. In contrast, several auxin-signaling mutants were more resistant to F. oxysporum which suggests that F. oxysporum requires components of auxin signaling and transport to colonize the plant more effectively (Kidd et al 2011). Hence, focusing on the role of auxin in banana defense response in future will help to understand the resistant mechanism against Foc.…”
Section: Auxinmentioning
confidence: 99%
“…In contrast to SA, some hormone-signaling pathways appear to promote disease susceptibility to F. oxysporum in Arabidopsis. Several components of Arabidopsis auxin-signaling pathways and polar auxin transport processes, but not auxin biosynthesis itself, have been shown to be required for full virulence of F. oxysporum on Arabidopsis (Kidd et al, 2011), suggesting a link between infection and development ). Application of abscisic acid (ABA), a plant hormone usually associated with abiotic stress responses such as water deficit, stimulated increased Fusarium wilt disease development in Arabidopsis while mutations in ABA biosynthesis genes promoted resistance (Anderson et al, 2004).…”
mentioning
confidence: 99%
“…Because F. oxysporum infects via the roots it would be expected that key signaling events determining resistance and susceptibility are initiated by both host and pathogen in root tissues early on during infection. The JA-signaling pathway and downstream responses, but not those of the SA pathway, appear to be activated in both the roots and leaves of Arabidopsis during infection by F. oxysporum (Edgar et al, 2006;Thatcher et al, 2009;Kidd et al, 2011). Activation of JA-regulated genes in leaves was also observed within 24 h after inoculation (Kidd et al, 2011), prior to the invasion of foliar tissues by the fungus, suggesting that systemic signals of host and/ or pathogen origin are most likely transmitted from root to shoot during F. oxysporum infection.…”
mentioning
confidence: 99%